2023
DOI: 10.1007/s11663-023-02827-z
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Mechanisms During Melting of H-DRI Focusing on Slag Formation and the Behavior of Vanadium

Abstract: The reaction mechanisms during melting of hydrogen direct reduced iron pellets (H-DRI) with different degrees of reduction were studied experimentally at 1773 K to 1873 K at different times (60 to 600 seconds), focusing on the autogenous slag formation. It was found that an autogenous slag is formed inside the pellets prior to the melting of the metal phase. The formation of the autogenous slag started with the melting of FeO, initially located in the center of the iron grains. The liquid FeO flowed into the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In an earlier work, observations of hydrogen reduced commercial iron ore pellets showed that the other oxides found inside the iron ore pellet before reduction were not reduced and remained inside the completely reduced pellet. [30] Therefore, the mass of the nonferrous oxides is considered constant, and the content is according to sample analysis. Multiple experiments were conducted to confirm the repeatability of the experimental procedure.…”
Section: Resultsmentioning
confidence: 99%
“…In an earlier work, observations of hydrogen reduced commercial iron ore pellets showed that the other oxides found inside the iron ore pellet before reduction were not reduced and remained inside the completely reduced pellet. [30] Therefore, the mass of the nonferrous oxides is considered constant, and the content is according to sample analysis. Multiple experiments were conducted to confirm the repeatability of the experimental procedure.…”
Section: Resultsmentioning
confidence: 99%